Development of Problem-Based HOTS (Higher Order Thinking Skill) Question Instruments on Class VIII Pressure Material - Irawati, Rina; Sukarmin, S; Yamtinah, Sri (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The HOTS question instrument is important in learning. Through HOTS students are trained to learn things at a higher level, think critically in receiving information, think creatively in problem solving, and make the right decisions in complex situations. These various abilities are certainly needed in the face of changing life dynamics. This situation requires us to continue to adapt, so the ability of HOTS is very important to be developed as an effort to improve the ability to think at a higher level and prepare ourselves to face problems in life. This makes the author interested in developing a problem-based HOTS problem instrument on pressure material. This research uses R&D techniques that refer to Thiagarajan's (1974) 3-D procedural model. The instrument consists of 10 description questions that refer to 5 indicators, namely: analyzing; Evaluate; Created; Troubleshooting; and critical thinking skills. The instrument was validated by 7 experts with the validity analysis technique Aiken (1950). The results of the analysis obtained: suitability of the question with bloom's taxonomy (88%), suitability of the question with the answer (86%), feasibility of language (85%); and the feasibility of presenting the question (84%). This proves that all aspects of the instrument are declared valid because Vcount > Vtable Aiken, Vtable Aiken 75%, so it is concluded that this instrument is declared valid and feasible to be used to test the higher-order thinking skills of learners.